Probing the cooperative mechanism of the μ–δ opioid receptor heterodimer by multiscale simulation. Issue 47 (27th November 2018) - Wang, Longrong; Yuan, Yuan; Chen, Xin; Chen, Jiangfan; Guo, Yanzhi; Li, Menglong; Li, Chuan; Pu, Xuemei
Abstract : The activation-cooperativity of the μ–δ opioid receptor heterodimer was probed by multiscale simulation coupled with a protein structure network. Abstract : Accumulated experimental evidence indicated that G-protein coupled receptors (GPCRs) could form biologically relevant oligomers and hetero-oligomers possess different functional properties from monomers and homo-oligomers, for example, unique pharmacology. However, the urgent lack of crystal structures of the GPCR oligomers results in very limited knowledge about their structural and functional mechanisms. In this work, we utilized a multiscale simulation strategy coupled with principal component analysis, correlation analysis and a protein structure network to study the hetero-dimerization of the μ-OR and δ-OR. We probed the cooperative mechanism involved in their activations, the allosteric communication pathways, the impact of the interface and differences from the μ-OR homodimer. The result indicates that TM1–TM2–H8 is a stable interface, but some residues of TM7 also participate in the dimer interface. Similar to the homodimer, the hetero-dimerization of the two inactive receptors would enhance the constitutive activation of one subunit but weaken that of the other subunit, both presenting a negative cooperativity. However, in contrast to the homodimer, the hetero-dimerization of the active protomer with the inactive one would weaken the constitutive activation of the inactive unit but maintain the activity of the active subunit. In addition, the hetero-dimerization and the activation of one subunit could significantly alter the types and the numbers of residues participating in the allosteric pathway from the ligand-binding pocket to the G-protein region and the pathway between two subunits. Some important residues were identified, which play important roles in modulating activations and cooperativity between two subunits. The observations from this work indicate that the negative cooperativity should be a common feature for the homodimers and the heterodimers, but the cooperative results would be significantly different between them, depending on the activated extent of one subunit.